The effectiveness of molnupiravir for treatment in patients with Covid-19: a systematic review (Research, Society and Development, 2022)
In early 2020, the outbreak of (SARS-CoV-2), the vírus that causes Covid-19, spread rapidly around the world, so much so that the World Health Organization (WHO) declared it a pandemic. There was great concern, as there was still no knowledge about this new pathology and many countries did not have a strategic health plan. Therefore, this article aims to verify the efficacy of this drug in clinical studies. It is a systematic review, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. The search strategy was designed using following controlled descriptors: Medical Subject Headings (MeSH) and Health Science Descriptors (DeCS) resources. The combinations of the descriptors resulted in the following terms: "Molnupiravir", "Covid-19" and "Sars-cov-2". In addition, the Boolean operators "OR" and "AND" were applied. The databases used were Medline, Lilacs, both via the Virtual Health Library (VHL); PUBMED; Scientific Electronic Library Online (Scielo); Science Direct and Google Scholar. Molnupiravir can be used as a prophylactic measure, thus preventing hospitalization; in hospitalized patients with comorbidities, this drug has no clinical benefit. SInce the sample sizes in the studies were averagely low, there is a need for further studies to be carried out and replicated to verify if molnupiravir is effective against Covid-19.